Pengaruh Promosi dan Citra Merek Terhadap Keputusan Pembelian Sepatu Bata di Tangerang Selatan - Muratin (Prisani Cendekia, 2022)
Competition makes innovation and creativity of company management continue to race, accurate marketing strategies must be prepared in order to achieve sales targets. Programs that are quite effective in communicating products in order to attract product purchase decisions are through promotional programs and a positive brand image in the minds of consumers. This study aims to determine the effect of promotions and company brand image on purchasing decisions for Bata shoes to consumers located in South Tangerang during February 2022. The research sample was 100 respondents with the method used in selecting the respondents was purposive sampling. The analytical tool used is multiple linear regression with the help of SPSS 25.00 which is the data analysis technique used. The results of the analysis show that promotion and brand image have a significant effect on.